Development of Homozygous Lines by In Vivo Doubled Haploid Technique in Hybrid Maize Breeding - İbrahim Cerit; Gönül Cömertpay; Bülent Çakır; Rüştü Hatipoğlu; Hakan Özkan (Turkish Journal of Agriculture: Food Science and Technology, 2023)
The maize breeding programs focuses on the development of homozygous parental lines for hybrid breeding to obtain heterosis. The Improvement of homozygous lines in a effective time is crucial for hybrid maize breeding. Objectives of this research were to obtain homozygous lines of maize in a short time by using of in-vivo maternal haploid (DH) technique and characterizing them morphologically. The experiments were carried out at the Eastern Mediterranean Agricultural Research Institute(EMARI). Inducers, RWS, RWK-76 and their hybrid RWS X RWK-76 were used as male parent. As female parent, 56 F2 segregated material obtained by selfing of 66 F1 hybrids developed in maize breeding program of Eastern Mediterranean Agricultural Research Institute (EMARI) and 2 F2 segregated material selected from the open pollinated plants of 9 commercial maize variety. As a result of the experiment, 29 doubled haploid lines (DH) were developed. In the developed DH lines, days to tasseling, plant height, height of first ear , ear length, ear diameter, number of kernel per ear and thousand kernel weight varied as 57-78 days, 151-248 cm, 43-112 cm, 11.20-24.50 cm, 24-45 mm, 224-537 kernels/ear, and 180-320 g, respectively. In conclusion, in-vivo maternal DH technique is a highly effective method for obtaining homozygous lines